Pembuatan Simulator Power Steering Beserta Troubleshooting - Riezky Idvi Alfitra; Ruzita Sumiati; Nusyirwan Nusyirwan; Adriansyah Adriansyah (Jurnal Teknik Mesin, 2019)
In this Final Project report, a little is explained about the parts of power steering and how to make the vehicle comfortable, especially when the vehicle turns. Stability and comfort in driving a vehicle is very important and desirable for all motorists, how it can be obtained. Power steering makes the driver feel light in controlling his vehicle especially when turning. So power steering is one of the things that is very important to get driving comfort. Therefore maintenance of the power steering is also important to be able to help realize stability and comfort in driving. In addition to the care also considered in the use of spare parts must be in accordance with the standards used in the vehicle